Sustainablility of Hospitality Industri, Opportunities and Obstacles Case Study: Food Waste Mitigation - Denny Arifiandi; Dudi Permana (Journal of Sustainable Economic and Business, 2026)
This study aims to analyse the influence of sustainability practices in increasing competitiveness in Indonesia, especially in the hospitality industry, with a primary focus on strategies for managing food waste generated by hotels. Globally, awareness of environmental issues is growing very well, and the hospitality industry (horeca: hotels, restaurants, cafes) is expected to contribute significantly to sustainability activities but also improve its position in the market. Through a quantitative method approach with a sample of 214 hotels in Jabodetabek, it is hoped that this study can analyse the sustainability initiatives that have been carried out to date and the resulting impacts, especially their influence on increasing business process efficiency, customer satisfaction and brand reputation. Market pressure, internal business processes and food waste mitigation, as well as hotel commitment to Sustainable Development are key factors measured in this study. The research findings show that hotels that are actively involved in food waste mitigation show improved operational performance, cost savings, and increased customer loyalty. In addition, this study identifies key factors that facilitate the successful implementation of sustainability practices, including staff contributions to business process efficiency, stakeholder engagement in production processes, and the use of technology that can provide hotel operational efficiency. This research contributes to the understanding of how sustainable practices can serve as a competitive advantage in the hospitality industry in the future, and offers practical recommendations for hotel management and policymakers to promote a more sustainable and resilient hospitality sector in Indonesia and globally. This study recommends that the government develop incentive policies for hotels that implement food waste mitigation practices and require sustainability certification as a hotel operational requirement. Hotel management needs to integrate waste tracking and AI forecasting technology, strengthen employee training, and build collaboration with food banks for the redistribution of food suitable for consumption